Penetrasi Natrium Bisulfit dan Kalium Sorbat Ke Dalam Nanas Selama Perendaman dan Pengaruhnya Terhadap Produk Nanas - Tyas Utami; Sri Anggrahini; Eni Harmayani; Sri Raharjo; Riri Iramani (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1996)
Preservation process of pineapple was carried out through combination of blanching, reduction of pH, addition of sugar and chemical preservatives and vacuum packaging. The effectivity of chemical preservatives used was influenced by their penetration into pineapple. The aims of this study were to investigate penetration effectivity of sodium bisulphite into pineapple in the presence of potassium sorbate and their influence to the product during storage. Prepared pineapples were soaked in solution (pH 3,0) containing of 40% w/v sucrose, with various concentrations of sodium bisulphite (100-500 ppm) and potassium sorbate (0-1500 ppm) for 24 hours. The products were packed in vacuum plastic and stored in room temperature. The result showed that penetration of sodium bisulphite into pineapple was greatly influenced by potassium sorbate concentration. On the other hand, penetration of potassium sorbate into pineapple was not significantly affected by sodium bisulphite concentration. Combination of sodium bisulphite (100-500 ppm) and potassium sorbate (0 and 500 ppm) could not prevent spoilage, as indicated by the swelling of vacuum plastic container. The use of 1000 ppm and 1500 ppm potassium sorbate produced no swollen package during two weeks storage. Concentration of vitamin C in the products treated with 1000-ppm potassium sorbate and sodium bisulphite (100-500 ppm) decreased during the two weeks storage. Treatment with 400 ppm and 500 ppm sodium bisulphite and 1000 ppm potassium sorbate could prevent browning reaction during two weeks storage.